Dietary ecology and niche differentiation of Pliocene-Pleistocene papionins from the Turkana Basin inferred from buccal dental microwear texture analysis and machine-learning approaches - Luis Hidalgo-Trujillo; Ferran Estebaranz-Sánchez; Albert E Dyowe-Roig; Ignacio Bayón Jiménez-Ugarte; Xabier Albizu-Arias; David Ríos-Insúa; Juan José Ibáñez; Alejandro Pérez-Pérez; Jaime Pizarroso; Berta Ruesca-Bonet; Simón Rodríguez-Santana; Laura M Martínez (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Assessment of EnMAP data quality through global product validation activities - Maximilian Brell; Philipp Reiners; Luis Guanter; Karl Segl; Sabine Chabrillat; Daniel Scheffler; Mariana A. Soppa; Niklas Bohn; Javier Gorrono; Alexander Kokhanovsky; Astrid Bracher; Martin Bachmann; et al. (Remote Sensing of Environment, 2026)

Trends and risk factors of antimicrobial resistance of Neisseria gonorrhoeae in Catalonia, Spain, 2022–2023 - Mercè Herrero; Sonia Broner; Naiana Pastrana-Batalla; Eduard Anfruns; Evelin López-Corbeto; Victoria González; Judit Serra-Pladevall; Nieves Larrosa; Jacobo Mendioroz; Pilar Ciruela; Yuliya Poliakova; Mateu Espasa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Longitudinal evidence for the emergence of multiple intelligences in assistance dog puppies - Hannah Salomons; Morgan Ferrans; Candler Cusato; Kara Moore; Vanessa Woods; Emily Bray; Brenda Kennedy; Theadora Block; Laura Douglas; Ashton Roberts; Margaret Gruen; Brian Hare (Animal Behaviour, 2026)

Understanding the spatio-temporal variability of fisheries data for better bottom trawling management practices in the Catalan margin (NW Mediterranean Sea) - Marta Carreton; Eve Galimany; Marta Blanco; Mariona Garriga-Panisello; Ana I. Colmenero; Marc Balcells; Ferran Bustos; Mireia G. Mingote; Cristina López-Pérez; David Nos; Xènia Puigcerver-Segarra; Marta Pujol-Baucells; et al. (Marine Policy, 2025)

The EnMAP spaceborne imaging spectroscopy mission: Initial scientific results two years after launch - Sabine Chabrillat; Saskia Foerster; Karl Segl; Alison Beamish; Maximilian Brell; Saeid Asadzadeh; Robert Milewski; Kathrin J. Ward; Arlena Brosinsky; Katrin Koch; Daniel Scheffler; Stephane Guillaso; et al. (Remote Sensing of Environment, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Diet in the Early Bronze Age: a buccal microwear analysis from the plain of Barcelona (Spain) - Alicia Gluitz; Laura M. Martínez; Miquel Molist; Ferran Estebaranz-Sánchez (Archaeological and Anthropological Sciences, 2023)
This study aims to characterize the dietary habits of the Barcelona plain (Spain) population during the Early Bronze Age. An analysis of buccal microwear has been performed on 467 samples from 20 individuals buried in the largest cemetery of the plain of Barcelona in this period, the Plaça de la Gardunya, and 1 sample from the site of the Mercat de Santa Caterina. Molars and premolars were examined using a scanning electron microscope (SEM), and their microwear patterns were compared with reference patterns associated with known dietary habits and subsistence strategies. The results suggest that dietary habits differed between age groups and between sexes: males were more carnivorous than females, and subadults ate harder foods than adults. Buccal microwear from the Barcelona plain shows similar values to carnivorous diets of anthropological populations. Based on all the archaeological evidence (building types and zooarchaeology, archaeobotany and stone tools) from this settlement and those in its vicinity, we propose that the individuals from the Barcelona plain had a mixed diet, with large consumption of meat, secondary products and fish. Agricultural products, stored in silos and grill structures and processed with more sophisticated grinding techniques, were also consumed, mainly by subadult individuals.

The EnMAP imaging spectroscopy mission towards operations - Tobias Storch; Hans-Peter Honold; Sabine Chabrillat; Martin Habermeyer; Paul Tucker; Maximilian Brell; Andreas Ohndorf; Katrin Wirth; Matthias Betz; Michael Kuchler; Helmut Mühle; Emiliano Carmona; et al. (Remote Sensing of Environment, 2023)

Defective Ru-doped α-MnO2 nanorods enabling efficient hydrazine oxidation for energy-saving hydrogen production via proton exchange membranes at near-neutral pH - Zhipeng Yu; Chaowei Si; Ferran Sabaté; Alec P. LaGrow; Zhixin Tai; Vlad Martin Diaconescu; Laura Simonelli; Lijian Meng; Maria J. Sabater; Bo Li; Lifeng Liu (Chemical Engineering Journal, 2023)

A continuous in silico learning strategy to identify safety liabilities in compounds used in the leather and textile industry - Eric March-Vila; Giacomo Ferretti; Emma Terricabras; Inés Ardao; José Manuel Brea; María José Varela; Álvaro Arana; Juan Andrés Rubiolo; Ferran Sanz; María Isabel Loza; Laura Sánchez; Héctor Alonso; et al. (Archives of Toxicology, 2023)
There is a widely recognized need to reduce human activity's impact on the environment. Many industries of the leather and textile sector (LTI), being aware of producing a significant amount of residues (Keßler et al. 2021; Liu et al. 2021), are adopting measures to reduce the impact of their processes on the environment, starting with a more comprehensive characterization of the chemical risk associated with the substances commonly used in LTI. The present work contributes to these efforts by compiling and toxicologically annotating the substances used in LTI, supporting a continuous learning strategy for characterizing their chemical safety. This strategy combines data collection from public sources, experimental methods and in silico predictions for characterizing four different endpoints: CMR, ED, PBT, and vPvB. We present the results of a prospective validation exercise in which we confirm that in silico methods can produce reasonably good hazard estimations and fill knowledge gaps in the LTI chemical space. The proposed protocol can speed the process and optimize the use of resources including the lives of experimental animals, contributing to identifying potentially harmful substances and their possible replacement by safer alternatives, thus reducing the environmental footprint and impact on human health.

Analysis of fingerprints on a PPNB figurine from the Tell Halula site, Syria - Albert Epitié Dyowe Roig; Ferran Estebaranz-Sánchez; Laura M. Martínez; Miquel Molist Montaña (Archaeological and Anthropological Sciences, 2023)
With the advent of the Neolithic, the first manipulation of clay for various purposes was observed. Fingerprints could be imprinted due to the plastic properties of clay. Their study and analysis can allow the estimation of the sex and age of the person who left them, thus providing insight into the social organisation of past populations. In the present study, we have analysed the fingerprints that were identified on a figurine representing a bovine animal found at the Neolithic site of Tell Halula in Syria. Tell Halula has a long period of occupation, from the Middle Pre-Pottery Neolithic B (PPNB) to the Late PPNB, with some of the earliest evidence of monumental and/or collective architecture. To confirm the human origin of the prints, the presence of minutiae was first identified. In order to estimate the sex and age of the individual, both the Mean Epidermal Ridge Breadth and the Ridge Breadth were calculated. The mean ridge widths were 0.52 ± 0.076 for the first fingerprint and 0.50 ± 0.11 for the second fingerprint. The ridge density was found to be 6.5. The results indicated that the maker of the bovine figurine could be an adult male (~18/20 years old), taking both values into account. The results suggest that it is highly likely that the individual who handled the artefact was an adult male. However, given the small number of fingerprints in the Tell Halula figurine collection, little more can be said. Not much can be inferred about social structure and division of labour. There is therefore a need for further research into both the symbolism of the objects and who was responsible for their production.

Clinical impact of rare variants associated with inherited channelopathies: a 5-year update - Georgia Sarquella-Brugada; Anna Fernandez-Falgueras; Sergi Cesar; Elena Arbelo; Mónica Coll; Alexandra Perez-Serra; Marta Puigmulé; Anna Iglesias; Mireia Alcalde; Marta Vallverdú-Prats; Victoria Fiol; Carles Ferrer-Costa; et al. (Human Genetics, 2022)
A proper interpretation of the pathogenicity of rare variants is crucial before clinical translation. Ongoing addition of new data may modify previous variant classifications; however, how often a reanalysis is necessary remains undefined. We aimed to extensively reanalyze rare variants associated with inherited channelopathies originally classified 5 years ago and its clinical impact. In 2016, rare variants identified through genetic analysis were classified following the American College of Medical Genetics and Genomics’ recommendations. Five years later, we have reclassified the same variants following the same recommendations but including new available data. Potential clinical implications were discussed. Our cohort included 49 cases of inherited channelopathies diagnosed in 2016. Update show that 18.36% of the variants changed classification mainly due to improved global frequency data. Reclassifications mostly occurred in minority genes associated with channelopathies. Similar percentage of variants remain as deleterious nowadays, located in main known genes ( SCN5A, KCNH2 and KCNQ1 ). In 2016, 69.38% of variants were classified as unknown significance, but now, 53.06% of variants are classified as such, remaining the most common group. No management was modified after translation of genetic data into clinics. After 5 years, nearly 20% of rare variants associated with inherited channelopathies were reclassified. This supports performing periodic reanalyses of no more than 5 years since last classification. Use of newly available data is necessary, especially concerning global frequencies and family segregation. Personalized clinical translation of rare variants can be crucial to management if a significant change in classification is identified.

Valorization of Marine Waste: Use of Industrial By-Products and Beach Wrack Towards the Production of High Added-Value Products - Vita Rudovica; Ana Rotter; Susana P. Gaudêncio; Lucie Novoveská; Füsun Akgül; Linn Kristin Akslen-Hoel; Diogo A. M. Alexandrino; Olga Anne; Lauris Arbidans; Miroslava Atanassova; Magdalena Bełdowska; Jacek Bełdowski; et al. (Frontiers in Marine Science, 2021)
Biomass is defined as organic matter from living organisms represented in all kingdoms. It is recognized to be an excellent source of proteins, polysaccharides and lipids and, as such, embodies a tailored feedstock for new products and processes to apply in green industries. The industrial processes focused on the valorization of terrestrial biomass are well established, but marine sources still represent an untapped resource. Oceans and seas occupy over 70% of the Earth’s surface and are used intensively in worldwide economies through the fishery industry, as logistical routes, for mining ores and exploitation of fossil fuels, among others. All these activities produce waste. The other source of unused biomass derives from the beach wrack or washed-ashore organic material, especially in highly eutrophicated marine ecosystems. The development of high-added-value products from these side streams has been given priority in recent years due to the detection of a broad range of biopolymers, multiple nutrients and functional compounds that could find applications for human consumption or use in livestock/pet food, pharmaceutical and other industries. This review comprises a broad thematic approach in marine waste valorization, addressing the main achievements in marine biotechnology for advancing the circular economy, ranging from bioremediation applications for pollution treatment to energy and valorization for biomedical applications. It also includes a broad overview of the valorization of side streams in three selected case study areas: Norway, Scotland, and the Baltic Sea.

Integrative Multi-omics Analysis to Characterize Human Brain Ischemia - Laura Ramiro; Teresa García-Berrocoso; Ferran Briansó; Leire Goicoechea; Alba Simats; Víctor Llombart; Ricardo Gonzalo; Alexandre Hainard; Elena Martínez-Saez; Francesc Canals; Jean-Charles Sanchez; Alex Sánchez-Pla; et al. (Molecular Neurobiology, 2021)

Buccal dental microwear variability in extant African Hominoidea: taxonomy versus ecology - Jordi Galbany; Ferran Estebaranz; Laura M. Martínez; Alejandro Pérez-Pérez (Primates, 2009)

Influence of Ground Predators on the Survival of the Mediterranean Fruit Fly Pupae, Ceratitis capitata, in Spanish Citrus Orchards - Alberto Urbaneja; Ferran García Marí; David Tortosa; Cristina Navarro; Pilar Vanaclocha; Laura Bargues; Pedro Castañera (BioControl, 2006)

Novel Approaches to Study Climate Change Effects on Terrestrial Ecosystems in the Field: Drought and Passive Nighttime Warming - Claus Beier; Bridget Emmett; Per Gundersen; Albert Tietema; Josep Peuelas; Marc Estiarte; Carmen Gordon; Antonie Gorissen; Laura Llorens; Ferran Roda; Dylan Williams (Ecosystems, 2004)